Distribution of fungal agents in the respiratory system of patients with underlying lung diseases; molecular identification and antifungal susceptibility profiles - Parviz Hassanpour; Seyed Jamal Hashemi; Sanam Nami; Roshanak Daie Ghazvini; Behrouz Naghili Hokmabadi; Abbas Rahimi Foroushani; Kazem Ahmadikia; Zahra Ramezanalipour; Saeid Firouzi Abriz (Iranian Journal of Microbiology)
Background and Objectives: Airway fungal infection is a severe clinical problem, especially in patients with compromised immune functions. Here, we examined the distribution and antifungal susceptibility profiles of fungal agents isolated from respiratory tract of symptomatic patients hospitalized in pulmonary units. Materials and Methods: This descriptive cross-sectional study took place from 2023 to 2024, involving 360 patients. Bronchoalveolar lavage (BAL) or sputum specimens were collected and analyzed using mycological and molecular methods for this study. Antifungal susceptibility testing (AFST) was carried out using the broth micro dilution method. Results: Of a total of 360 respiratory specimens, 114 (31.6%) were positive. The male-to-female ratio was 63:51 (1.3%). Candida albicans and Aspergillus flavus were the most common yeast and mold species. Chronic obstructive pulmonary disease (COPD) had the highest rate of colonization with fungal agents (47/114, 41%). The isolates associated with COPD in this study included Aspergillus species (4/12, 3.5%), Candida species (41/96, 36%), and other fungal species (2/6, 1.5%). Coughing (87%) was the predominant symptom, and malignancy (52%) was the predominant comorbidity factor. The result of AFST for antifungal agents showed that 9 (22.5%) Candida isolates were resistant, and the highest rate of resistance was related to voriconazole agent (5/9, 55.5%). Resistance to antifungal agents was not observed among Aspergillus isolates. Conclusion: This study showed a significant relationship between the frequency of Aspergillus and Candida species in patients with underlying lung diseases. In addition, voriconazole was more effective than itraconazole, especially against Aspergillus flavus.